Evaluating the effects of yeast isolates on the control of sore shin in tobacco (Nicotiana tabacum L.) seedlings - Timbe, Isaac Simbarashe (2018)
Sore shin aused by Rhizoctonia solani is responsible for remarkable economic losses of up to 10% in tobacco (Nicotiana tabacum) seedlings grown in float beds, thereby becoming important production limiting factor of tobacco crop. Sore shin is responsible for wiry stem formation, stem lesions, root rots, root discolouration and damping off of tobacco seedlings. Tobacco production in Zimbabwe contributes about 9% GDP and is form of employment to more than 90 000 people in the country. Currently two fungicides Shavit and Azoxystrobin are being used for controlling sore shin on tobacco but recent trends are showing element of resistance with R. solani therefore becoming a threat. In a bid to circumvent the tobacco losses due to sore shin using eco-friendly methods the researcher hereby sought to evaluate five yeasts isolates for the control of sore shin in greenhouse produced tobacco seedlings. In this study five isolates were used which are TY5, TY3, TY14, TY17 and TY18, the experiment was arranged in a completely randomised design and two controls were included with the untreated as negative control and Azoxystrobin as positive control. R. solani were isolated from the diseased tobacco plants showing sore shin symptoms. The experiment was carried out at Kutsaga Research Station located in Harare Zimbabwe during the September –November 2016 tobacco nursery period. Data was analysed using Genstat 18th edition, on parameters measured the yeast isolates proved to reduce sore shin significantly in comparison with the untreated control but TY18 was similar to the untreated control. The isolates resulted in an increase in shoot fresh weight with the highest recorded on TY3 with an average of 3.76g per seedling, also yeast isolates resulted in an increase root fresh weight, highest weight was recorded on seedlings treated TY5 but TY18 was even less than the untreated control. Significant increase in dry weight was observed on plants treated with yeast isolates seedlings plots treated with TY3 recorded the highest dry weight with an average of 0.39g per seedling. It could be suggested that such yeast isolates might be the promising as alternatives for controlling sore shin on tobacco seedlings and have the ability to be used as bio-fertilisers